Dampak Jumlah Pengusaha Kena Pajak (PKP) dan Faktor Makro Ekonomi terhadap Penerimaan Pajak Pertambahan Nilai (PPN) di KPP Pratama Cikarang Selatan - Asiah, Neng; Yahya, Adibah; Fuadi, Agus; Khasanah, A'an Nur (LPPM Universitas Pelita Bangsa, 2023)
This research aims to determine the factors influencing value-added tax (PPN) revenue, which includes the number of taxable entrepreneurs (PKP) and macroeconomic factors measured through inflation and the exchange rate of the Indonesian rupiah. The data sample used in this study consists of monthly reports from 2019 to 2021. Hypothesis testing was conducted using multiple regression, and the research results indicate that simultaneously, the number of PKP, inflation, and the exchange rate have a significant influence on PPN revenue. However, when observed individually, only the inflation variable positively affects PPN revenue. On the other hand, the number of PKP and the exchange rate do not significantly impact PPN revenue. The variables of the number of PKP, inflation, and the exchange rate can collectively explain 38.1% of the variance in value-added tax revenue.